Pseudo-leptospires in broncho-alveolar lavage fluid and blood cell cultures. - Williams, W. R. (1986)
Two types of microscopic filaments were observed in mucous and fluid obtained by broncho-alveolar lavage (BAL). Filaments in mucous smears were probably cilia from desquamated ciliated epithelial cells. Those in BAL fluid, resembling leptospira, may originate from platelets as similar filaments were produced in vitro by exposing platelets to thrombin.